Reinventing Government Pelayanan Mobil Siaga Desa - Retno, Diyah Norisa; Huda, Muhammad Miftahul; Junadi, Junadi (Public Policy, 2024)
As a state apparatus, it is mandatory to provide quality public services to the community. Service innovation that continues to be carried out makes its own satisfaction value for the community as service recipients. Reinventing government is one of the principles of apparatus performance in New Public Management (NPM) which is a reference for bureaucrats to provide more modern and guaranteed public service innovations. Health services are the most important thing in life, especially in terms of health transportation. The standby car is an example of innovation in health service transportation from the government to be provided to the community to facilitate community facilities and infrastructure in obtaining services. This research on the standby car was conducted to examine the use of reinventing government principles in the village standby car service. This research uses descriptive methods with interviews and observations. Data sources were obtained from the Social Service and the person in charge of managing the village standby car. The findings of this study are that there are still several indicators that are not fulfilled if the standby car service system refers to the principles of reinventing government.